The Process of Investigation on Criminal Currency - Beni Aji; Lathifah Hanim (Law Development Journal, 2021)
The objectives of this study are as follows: To identify and analyze the investigation process of currency crimes. To find out and analyze obstacles to the process of investigating currency crimes. To find out and analyze solutions to overcome barriers to the investigation of currency crimes. The method used by researchers is juridical sociological approach to law and The specifications in this research are descriptive. Based on the results of that research The process of investigating currency crimes actions in the form of: (a) arrest; (b) Detention; (c) Confiscation of evidence; (d) Witness examination; (e) Examination of the suspect (f) Then a discussion is conducted in the form of case analysis and juridical analysis; (g) Making a resume by the assistant investigator/investigator and then drawing a conclusion. The obstacles are: First, the lack of coordination between law enforcement officers. Second, the weakness of investigations against perpetrators who are categorized as perpetrators. Third, investigations currently carried out by investigators are limited to the perpetrators who destroyed rupiah banknotes, resulting in difficulties in fulfilling the subjective element, namely mens rea. Solutions include: a) Overcoming crimes committed by the Indonesian National Police for destroying rupiah banknotes. b) Regional and international police cooperation can be carried out through Interpol, other government agencies or directly.